A 'pebble test of anxiety' did not differentiate between Japanese quail divergently selected for stress and fear - Jones, R. Bryan (2004)
It has been suggested that the time taken by an individually tested domestic chick to begin pecking at pebbles on the floor of a novel arena might be used as a test of fear and anxiety, with low latencies to peck indicating low fear and vice versa, and as a potential selection criterion 'to choose fowls with the best performance later in life' [Appl. Anim. Behav. Sci. 73 (2001) 102]. The present study tested the above hypotheses by comparing the responses of 1-day-old Japanese quail chicks from genetic lines known to show high (HS) or low (LS) levels of fearfulness when they were exposed individually to a similar test situation. Since social separation is a stressful event the quail were housed either individually (IND) or in groups (SOC) before test to establish whether the prior social environment influenced behaviour in the pebble test. The LS chicks walked sooner and more than HS ones but there were no line effects on pecking at the pebbles. Chicks that had been housed individually walked and pecked at the pebbles sooner than did those that were housed in a group prior to test, indicating that sudden isolation elicited greater fear in SOC than in IND quail. The higher levels of activity then shown by SOC than IND quail probably reflected greater social reinstatement motivation in socially housed birds. Although the inconsistency between the present results and those of Salvatierra and Arce [Appl. Anim. Behav. Sci. 73 (2001) 102] might simply reflect species differences, our findings sound a cautionary note and point to the need for further study before a pebble test could be confidently used to assess fearfulness. © 2004 Elsevier B.V. All rights reserved.